Molecular dynamics simulation of phase transition and crack propagation in metastable high entropy alloy. (December 2022) - Ya-zhou, Liu; Yun, Luo; Shuo, Su; Yan-yu, Song; Sheng-peng, Hu; Xiao-guo, Song; Ning, Guo; Wei-min, Long
Abstract: Crack propagation mechanisms and phase transformation play a crucial role in improving the formability of metastable high-entropy alloys (HEA). In this study, a multi-component single-crystal Ta 0.5 HfZrTi metastable high-entropy alloy with a single-sided corner crack is investigated during the stretching process by Molecular dynamics. Based on the stress state during stretching, crack propagation is divided into two groups, phase transition at the crack tip and crack growth. We are investigating the phase transformation behavior of metastable high-entropy alloys under different stress states by tensile and shear deformation of defect-free single crystals. This paper studies the crack propagation process by creating cracks of different angular sizes on the single side of a single crystal. The results explain the atomic motion pattern of the phase transformation in metastable high-entropy alloys from BCC to HCP structure and the reasons for creating FCC structures during the phase transformation. Tensile simulations of single crystals with single-sided cracks explain the relationship between crack propagation and phase transition. Graphical Abstract: ga1